Taxonomic and cytogenetic studies in Opuntia ser. Armatae (Cactaceae) - Las Peñas, Maria Laura (2017)
Opuntia series Armatae is evaluated considering morphological (vegetative, floral and carpological) and cytogenetical (diploid number, presence of heterochromatin and physical localization of ribosomal genes) features to shed light on their systematics and evolution. Three complexes (named O. elata, O. megapotamica and O. monacantha) are proposed to accommodate seven species according to the tepal, fruit, stigma and seed aril traits. Additional systematic conclusions include: 1. O. stenarthra, O. assumptionis, O. cognata and O. subsphaerocarpa are synonyms; 2. O. elata is a variable species with two varieties: var. cardiosperma and var. obovata; 3. O. rioplatense is a synonym of O. elata var. obovata and 4. O. megapotamica is a polymorphic species with two varieties (one newly described and a new combination). All species had small similar-sized symmetrical chromosomes and were tetraploid (2n=44), except for a population of O. arechavaletae and O. monacantha (2n=22). All showed one or two pairs with CMA+/DAPI?NOR associated bands. The 18-5.8-26S rDNA loci seem to coincide with CMA+/DAPI-/NORs blocks. The number of 5S signals detected was proportional to the ploidy level of the species. A combination of cytogenetic and morphological features helped to differentiate the complexes, species, and varieties of Opuntia ser. Armatae.